Improving the Business Performance of Entrepreneurial Students in Pamulang University Through the Digital Business Ecosystem - Martono, Adi; SafÃ'i, Mohammad (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
Students as an educated community group have a higher success rate in doing business. But they must be good at managing their time between running a business and studying. This research will focus on students who do business and the external factors that influence it. The object of research is students majoring in Accounting and Management, Faculty of Economics, Pamulang University who run a business. This study has several objectives, namely 1. to obtain a profile of these students in running their business. 2. get information on whether the campus environment can encourage their business development. This research is a qualitative research. Researchers used a questionnaire to collect information and data. The questionnaire is distributed online to students who have businesses. From the questionnaire, information was obtained that 47% of students sold their own products, more than 50% had been doing business for less than 1 year and more than 60% were micro entrepreneurs. Students use social media to market their products but they also need digital marketing training, on the other hand they agree that the marketplace can be a means to market products among the Pamulang University academic community. The conclusion is that Pamulang University, which has more than 70,000 students (source pddikti.kemendikbud.go.id), is a large market for students to sell their products and therefore needs to be supported by technology and a business ecosystem so that all of them can connected each others. Campus can cooperate with other parties to utilize technology such as marketplace.